Heroin use impairs smoking cessation among Australian prisoners - Indig, D.; Wodak, A.; Richmond, R.; Butler, Tony; Archer, V.; Wilhelm, K. (2013)
Background: Prisoners have extremely high rates of smoking with rates 3-4 times higher than the general community. Many prisoners have used heroin. The aims of this study were to investigate the impact of heroin use on smoking cessation and the social determinants of health among prisoners. Methods. Secondary analysis of data from a randomised controlled trial of a multi-component smoking cessation intervention involving 425 Australian male prisoners. Inmates who, prior to imprisonment, used heroin regularly were compared to those who did not use heroin regularly. Self-reported smoking status was validated at baseline and each follow-up by measuring carbon monoxide levels. Readings exceeding 10 ppm were defined as indicating current smoking. Results: Over half (56.5%) of the participants had ever used heroin while 37.7% regularly (daily or almost daily) used heroin in the year prior to entering prison. Prisoners who regularly used heroin had significantly worse social determinants of health and smoking behaviours, including lower educational attainment, more frequent incarceration and earlier initiation into smoking. Prisoners who regularly used heroin also used and injected other drugs significantly more frequently. At 12-month follow-up, the smoking cessation of prisoners who had regularly used heroin was also significantly lower than prisoners who did not regularly use heroin, a finding confirmed by logistic regression. Conclusions: Regular heroin use prior to imprisonment is an important risk factor for unsuccessful attempts to quit smoking among prisoners and is also associated with worse social determinants of health, higher drug use, and worse smoking behaviours. More effective and earlier smoking cessation interventions are required for particularly disadvantaged groups. Trial registration. This trial is registered with the Australian New Zealand Clinical Trials Registry 12606000229572. © 2013 Indig et al.; licensee BioMed Central Ltd.